The Edinburgh companion to modernism, myth and religion - Hobson, Suzanne; Radford, Andrew, 1972- (Edinburgh companions to literature and the humanities., 2023)
"Until fairly recently, the 'Authorised Version' of cultural modernism stated that the secularising trends of liberal modernity -- and the resultant emphasis on irony, parody and dissolution in modernist artforms -- had pushed religion to the edges of early twentieth-century culture. This Companion complicates this understanding by furnishing students and academic researchers with more nuanced and probing assessments of the intersections and tensions between religion, myth and creativity during this half century of geopolitical ferment. It addresses the variety and specificity of modernist spiritualities as well as the intricately textured and shifting standpoints that modernist figures have occupied in relation to theological traditions, practices, creeds and institutions. What emerges is a multi-textured account of modernism's deep-rooted concern with the historical and established forms of religion, as well as new engagements with 'occulture' and indigenous traditions. In short, the Companion supplies a lively and original exploration of the aesthetic, publishing, technological and philosophical trends that shape debates about spirituality, community and self from the 1890s to the 1940s and beyond"--